2015
DOI: 10.1016/j.schres.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

CX3CR1 is dysregulated in blood and brain from schizophrenia patients

Abstract: The molecular mechanisms underlying schizophrenia remain largely unknown. Although schizophrenia is a mental disorder, there is increasing evidence to indicate that inflammatory processes driven by diverse environmental factors play a significant role in its development. With gene expression studies having been conducted across a variety of sample types, e.g., blood and postmortem brain, it is possible to investigate convergent signatures that may reveal interactions between the immune and nervous systems in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 97 publications
2
44
0
Order By: Relevance
“…In combination with gene set and network-based analyses, identified emergent biological functions robustly altered in SZ brain and peripheral blood transcriptome. Our study is preceded by a recent meta-analysis that sought to identify a cross-tissue signature of SZ using postmortem brain and ex vivo peripheral blood microarray data (Bergon et al, 2015). Comparing the differentially expressed genes identified in the present study with those reported by Bergon et al ., we observe only eight brain and 40 blood genes implicated by both studies; differences in the results could be attributed to the following differences between studies: (1) inclusion of different postmortem brain regions (multiple regions vs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In combination with gene set and network-based analyses, identified emergent biological functions robustly altered in SZ brain and peripheral blood transcriptome. Our study is preceded by a recent meta-analysis that sought to identify a cross-tissue signature of SZ using postmortem brain and ex vivo peripheral blood microarray data (Bergon et al, 2015). Comparing the differentially expressed genes identified in the present study with those reported by Bergon et al ., we observe only eight brain and 40 blood genes implicated by both studies; differences in the results could be attributed to the following differences between studies: (1) inclusion of different postmortem brain regions (multiple regions vs .…”
Section: Discussionmentioning
confidence: 99%
“…A variety of practical and technical limitations may contribute to this, including: the evolution of new array technologies over time, the likelihood of etiologic heterogeneity of SZ (Arnedo et al, 2015; Tsuang and Faraone, 1995), the use of small sample sizes, and the inability to adequately protect against type-I errors, all of which exacerbate the “winner’s-curse” phenomenon that undermines replication. In light of these issues, several studies have sought to consolidate the knowledge of transcriptomic abnormalities in SZ via meta-analysis (Bergon et al, 2015; Mistry and Pavlidis, 2010; Mistry et al, 2013a; Pérez-Santiago et al, 2012). These studies bolstered confidence by employing consistent preprocessing methods and demonstrating some similar dysregulated genes and network features across different studies; the implicated biological functions included oxidative phosphorylation, protein and nucleotide metabolism, synaptic transmission, myelination and glial function, and immune function, each of which have been implicated in previous work (Åberg et al, 2006; Dean, 2011; Devor and Waziri, 1993; Fineberg and Ellman, 2013; Middleton et al, 2002; Potvin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression profiling studies in postmortem human samples have uncovered a wide array of cellular processes disrupted in schizophrenia patients (Horv ath and Mirnics, 2014;Bergon et al, 2015), including immune mechanisms (Arion et al, 2007;Saetre et al, 2007;Fillman et al, 2013). A recent meta-analysis of long-term antipsychotic monotherapy-stabilized patients (61.6% male, average age 50.5 years, and sex-and age-matched controls) examined blood and serum cytokine transcript levels and found elevated expression of numerous genes involved in inflammatory and wound response (Bergon et al, 2015).…”
Section: Schizophreniamentioning
confidence: 99%
“…Recently, it was reported that decreased CX3CR1 expression was associated with a decrease in the number of synapses in the schizophrenic post-mortem brain. 25 CX3CR1 expression was decreased in bipolar disorder peripheral monocytes, 26 whereas CX3CR1 expression was increased in the post-mortem prefrontal cortex of autism patients. 27 Thus far, no studies have investigated the associations between genetic variants of CX3CR1 and CNS disorders.…”
mentioning
confidence: 92%
“…The involvement of CX3CR1 in brain structure and susceptibility to psychiatric disorders has also been observed in clinical specimens. Recently, it was reported that decreased CX3CR1 expression was associated with a decrease in the number of synapses in the schizophrenic post‐mortem brain . CX3CR1 expression was decreased in bipolar disorder peripheral monocytes, whereas CX3CR1 expression was increased in the post‐mortem prefrontal cortex of autism patients .…”
mentioning
confidence: 99%